A CROSS-SECTIONAL STUDY ON MANDIBULAR SEXUAL DIMORPHISM FOR FORENSIC SEX DETERMINATION USING PANORAMIC RADIOGRAPHY IN A SOUTH INDIAN POPULATION (Journal of Forensic Medicine & Toxicology, 2025)
Sex determination is an important part of forensic identification, helping improve accuracy in determining age, height, and personal identity. The mandible, recognised for its durability and pronounced sexual dimorphism, is second only to the pelvic bone in sex estimation applications. This research seeks to evaluate the reliability of linear mandibular measures on panoramic radiographs for sex determination in a South Indian demographic. This cross-sectional research was performed at Jawaharlal Nehru Medical College in Belagavi, Karnataka. Panoramic radiographs of 250 people (125 men and 125 females) aged 20 to 40 years were examined. Radiographs obtained from August 2022 to August 2024 were chosen according to stringent inclusion criteria to guarantee precision, including whole mandibular structures. Recorded linear measures included minimum ramus width, projective height of the ramus, maximum ramus width, coronoid height, symphysis height, and mandibular corpus height. Statistical study, including independent t-tests and discriminant function analysis, was performed to identify significant differences between sexes and to develop sex estimation. Marked disparities were seen in all assessed parameters between men and females (p < 0.05), with males generally exhibiting higher mean values. Panoramic radiographs of the mandible provide a non-invasive and dependable technique for sex assessment in forensic applications, with elevated accuracy levels when several linear measures are used. These results underscore the need of population-specific reference models for forensic applications across various geographical locations.
Keywords: Sex estimation; Mandible; Panoramic radiograph; Forensic identification; Linear measurements